Isolation of probiotics Lactobacillus Acidophilus from Commercial yoghurt - Hassan, Hassan Pyar Ali (مجلة الأندلس للعلوم الاجتماعية والتطبيقية, 2023)
Probiotic lactic acid bacteria, being the most often used vehicle in microorganism, are commercialized mainly as food enhancement among dairy products. The number and the type of the probiotics are very essential in order to ensure the activity. In this study, a rapid screening method was used to isolate probiotic Lactobacillus strain from commercial product of yoghurt after enrichment in De-Man-Rogosa Sharpe (MRS) medium and nutrient medium. The Lactobacillus strain was then isolated and identified based on morphology identification. The result showed a significantly high yield of pure culture of Lactobacillus acidophilus obtained from MRS medium (viable number of the cell in the yoghurt was about 107 CFU/ml) than compare to the nutrient medium. In conclusion, MRS medium is suitable for isolation of Lactobacilli compared to nutrient medium.